Psychological and psychosocial interventions for refugee children resettled in high-income countries. (10th November 2017) - Fazel, M.
Abstract : Large numbers of refugee children are arriving in high-income countries. The evidence to date suggests that they have mental health needs that are higher than for the general population and that these are exacerbated by the numbers of traumatic events they have experienced and the post-migration stressors they continue to be exposed to. The importance of a thorough and thoughtful assessment is discussed. Treatments of note are described for post-traumatic stress disorder, family functioning, general mental health problems and school environments. Future opportunities to operationalise outcome measures, develop multimodal interventions and utilise implementation science methodology are considered.